2012
DOI: 10.1016/j.vetimm.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription abnormalities in canine atopic dermatitis and related human eosinophilic allergic diseases

Abstract: Canine atopic dermatitis (AD) is clinically similar to human AD, implicating it as a useful model of human eosinophilic allergic disease. To identify cutaneous gene transcription changes in relatively early inflammation of canine AD, microarrays were used to monitor transcription in normal skin (n = 13) and in acute lesional AD (ALAD) and nearby visibly nonlesional AD (NLAD) skin (n = 13) from dogs. Scanning the putative abnormally transcribed genes, several potentially relevant genes, some abnormally transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 23 publications
(31 reference statements)
3
32
0
Order By: Relevance
“…In fact, CCL17 was the highest-expressed gene in microarray and PCR assays at the 48-hour time point. This strong up-regulation of CCL17 has been previously reported in lesional human (Choy et al, 2012;Gittler et al, 2012) and canine AD skin (Maeda et al, 2002;Maeda et al, 2005;Plager et al, 2012), as well as after HDM challenges in sensitized dogs (Marsella et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In fact, CCL17 was the highest-expressed gene in microarray and PCR assays at the 48-hour time point. This strong up-regulation of CCL17 has been previously reported in lesional human (Choy et al, 2012;Gittler et al, 2012) and canine AD skin (Maeda et al, 2002;Maeda et al, 2005;Plager et al, 2012), as well as after HDM challenges in sensitized dogs (Marsella et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…In this dog model, HDM induced the up-regulation of genes coding for three mast cell proteases that could be involved in itch induction: chymase, tryptase, and the tryptase-like mastin; the latter being analogous to mouse mast cell protease-11 (Prss34) (note that their human homolog is only a pseudogene). Mastin has been shown previously to be up-regulated in acute canine AD skin (Plager et al, 2012), but its itch-inducing effect has not been studied in animal species in which this protein exists. Chymase has been shown to be a pruritogen in a single old publication (Hagermark et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…136 A microarray analysis in acute cAD skin lesions revealed that the transcription of il-33 was approximately three times higher than that in healthy dogs. 142 Transcription analyses by microarray and RT-qPCR demonstrated the increased transcription of il-33 in the skin of dogs sensitized to HDM allergens. 122 These results suggest that canine IL-33 is likely involved in the pathogenesis of cAD, similar to human AD.…”
Section: Interleukin-33: Il-33mentioning
confidence: 95%